Pengaruh Promosi dan Nilai Taksiran Terhadap Minat Nasabah Menggunakan Fasilitas Gadai Emas pada Bank Syariah Indonesia KC Prabumulih Sudirman 1 - Puspa Utami; Muhlisin Muhlisin; Kamalia Sani (LA RIBA: Jurnal Perbankan Syariah, 2026)
This study aims to examine the effect of promotion and appraisal value on customers' interest in using the gold pawn financing facility at Bank Syariah Indonesia (BSI) KC Prabumulih Sudirman 1. A quantitative approach was employed using a survey method involving 89 respondents, and the data were analyzed through linear regression using SPSS. The findings indicate that both promotion and appraisal value have a positive and statistically significant effect on customers' interest in utilizing the gold pawn facility. Promotion emerged as the more influential variable, with a t-value of 5.384 (p < 0.001), while appraisal value also demonstrated a significant effect, with a t-value of 4.353 (p = 0.001). These findings suggest that effective promotional strategies and competitive appraisal values play a crucial role in enhancing customers' intention to use gold pawn financing services. Therefore, Bank Syariah Indonesia should optimize its promotional activities and collateral appraisal policies to strengthen the competitiveness of its gold pawn products and increase customer interest.